Review of the Safety, Efficacy and Tolerability of Palivizumab in the Prevention of Severe Respiratory Syncytial Virus (RSV) Disease - O'Hagan S; Galway N; Shields MD; Mallett P; Groves HE (Drug, Healthcare and Patient Safety, 2023)
Shaun O’Hagan,1,2 Niamh Galway,3 Michael D Shields,3,4 Peter Mallett,1,4 Helen E Groves1,2 1Paediatric Infectious Diseases, Royal Belfast Hospital for Sick Children, Belfast, Northern Ireland; 2Wellcome-Wolfson Institute for Experimental Medicine, Queen’s University Belfast, Belfast, Northern Ireland; 3Paediatric Respiratory Medicine, Royal Belfast Hospital for Sick Children, Belfast, Northern Ireland; 4Centre for Medical Education, Queen’s University Belfast School of Medicine, Belfast, Northern IrelandCorrespondence: Helen E Groves, Email h.groves@qub.ac.ukAbstract: Respiratory Syncytial Virus (RSV) is a major global cause of childhood morbidity and mortality. Palivizumab, a monoclonal antibody that provides passive immunity against RSV, is currently licensed for prophylactic use in specific “high-risk” populations, including congenital heart disease, bronchopulmonary dysplasia and prematurity. Available research suggests palivizumab use in these high-risk populations can lead to a reduction in RSV-related hospitalization. However, palivizumab has not been demonstrated to reduce mortality, adverse events or length of hospital stay related to RSV. In this article, we review the management of RSV, indications for palivizumab prophylaxis, the safety, cost-effectiveness and efficacy of this preventative medication, and emerging therapeutics that could revolutionize future prevention of this significant pathogen.Keywords: RSV, palivizumab, efficacy, safety, future directions